EXAMINING PSYCHOLOGICAL TRAUMA IN ADULTS AND CONTRASTING IT WITH TRAUMA IN SHAKESPEARE'S HAMLET CHARACTER, PRINCE HAMLET - Bita Iraji (SocioEdu: Sociological Education, 2024)
Since unfortunate events can happen to anyone at any time, it is important for everyone to understand the concept of psychological trauma and be able to identify its symptoms to prevent or treat it before it becomes too late. The character of Hamlet is traumatized from the very beginning of the play, and as the story develops, so does his trauma. Shakespeare's Hamlet is a well-known and widely performed play, making it a good option to illustrate trauma and its detrimental consequences on both the individual and others around them in real life. The study, which was founded on the constructivist paradigm, demonstrated adult psychological trauma, its symptoms, and its effects by using a phenomenological approach. Twelve people, six men and six women, over the age of eighteen (from 19 to 60), participated in this study. After an analysis of the experiences and feedback provided by the participants, it became clear that if psychological trauma is not identified and treated in a timely manner, it can negatively impact not only the victim's own life but also the lives of those close to them and even society as a whole.